Persepsi Dampak dan Kesiapan Pelaksanaan Merdeka Belajar Kampus Merdeka Berdasarkan Analisis Dependensi Minat Mahasiswa dengan Pengetahuan - Dian Wijayanti; Rino Tam Cahyadi (Jurnal Kajian Ilmiah, 2023)
This study aims to examine the relationship between student interest and knowledge, perceptions of the impact of freedom of learning (MBKM program) implementation and the readiness of Study Programs and students in MBKM implementation. The survey was conducted on 138 respondents who are students of the Accounting Study Program, Ma Chung University. The data analysis method used is the dependency test. First, test the dependence of students' interests on their knowledge related to MBKM. Second, the dependency test of student interest with the perception of the impact of MBKM in terms of 4 (four) components, length of study, improvement of soft skills, fulfilment of needs after graduation, and enhancement of additional competencies. Third, the dependency test of student interest with MBKM readiness in terms of Study Program readiness and student readiness as MBKM participants. The results showed that there was a dependency between student interest and the perception of the impact of MBKM. Meanwhile, the dependency test between student interest and MBKM knowledge and readiness did not show significant results. Even though the MBKM program is perceived as useful, students' interest in participating is still considered low. The results of this study provide input to the Study Program to develop a more structured curriculum and improve the program socialization.